Effects of experimental calcium availability and anthropogenic metal pollution on eggshell characteristics and yolk carotenoid and vitamin levels in two passerine birds. (May 2016) - Espín, Silvia; Ruiz, Sandra; Sánchez-Virosta, Pablo; Salminen, Juha-Pekka; Eeva, Tapio
Abstract: The maternal investment into egg quality depends on the condition of the female, the quality of the mate, and the quality of the environment. In that sense, availability of nutrients and exposure to pollutants are essential parameters to consider. The main aim of this study is to assess the effects of calcium (Ca) availability and anthropogenic metal pollution on early-stage reproduction in two passerine species, great tits ( Parus major ) and pied flycatchers ( Ficedula hypoleuca ), inhabiting a Ca-poor and metal-polluted area in SW Finland. Both species were able to obtain sufficient Ca for eggshell formation, and metal pollution was below the level of having negative effects in the egg size and eggshell characteristics. However, metal polluted environment negatively affected yolk lutein and vitamin D3 levels in both species, probably because of a lower access to carotenoid-rich diet and higher metal interference with vitamin D3 metabolism. The higher levels of vitamin D3 in yolks in the unpolluted zone could also be due to upregulated D3 levels as a response to the lower natural Ca availability. Yolk carotenoids and vitamin D3 were positively associated with nestling growth and size, supporting their importance for the appropriate chick development. The interspecific differences in yolk nutrient concentrations possibly reflect the different growth rate of these species. Pied flycatchers are likely adapted to low Ca availability through an efficient vitamin D3 metabolism, but their Ca intake could be close to a deficient level. Highlights: Metal pollution affected maternal lutein and vitamin D3 allocation to yolk. Metal pollution did not affect the egg volume, eggshell index and pigmentation. Both species were capable to obtain sufficient calcium for eggshell formation. Nestling growth and size was influenced by carotenoids and vitamin D3 in yolk. The two species differ in their carotenoid and vitamin D3 investment into egg yolks.